PENGARUH ENSO TERHADAP VARIASI TAHUNAN PARTIKULAT HALUS (PM2,5) - Nani Cholianawati; Haries Satyawardhana; Dessy Gusnita; Waluyo Eko Cahyono (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Meteorologi Klimatologi dan Geofisika, 2020)
PM2,5 is a particle that is very small (diameter <2.5 Î¼m) and tends to last long enough in the air. If the particles are inhaled, humans can endanger the respiratory system. One of the main sources of PM2.5 is burning of vegetation. This study analyzes the annual variation of PM2,5 in the Indonesian region and studies the effect of ENSO on the variation of PM2,5. Besides that, it was also studied the relation of ENSO to these variations. For 17 years (1999 to 2015), PM2.5 showed the highest annual average in 2015 in Indragiri Hulu Regency (Riau Province) of 81 Âµg / m3 far compared to Indonesia's annual PM2.5 standard of 15 Î¼g / m3. The occurrence of land fires is a source of PM2.5 in the eastern part of Sumatra (Riau Province, South Sumatra, and Jambi) and central Kalimantan. The north coast of Java also has PM2.5 which is high every year. The locations with the highest PM2.5 in the region are in Indramayu Regency, around 17 to 28 Î¼g / m3. During El Nino (2002, 2006 and 2015), annual PM2.5 concentrations increased significantly, while during La Nina (1999, 2007, 2010), PM2.5 concentrations decreased.